The Politics of Racial Disparity Reform: Racial Inequality and Criminal Justice Policymaking in the States - Donnelly, Ellen A. (American journal of criminal justice, 2017)
Racial inequalities in criminal justice are pressing problems for policymakers. Prior literature suggests elected officials promulgate punitive, racially disparate criminal justice policies due to partisanship and racial fears, but scholarship has yet to explain how and why elected officials address racial problems in criminal processing. This article introduces the framework of racial disparity reform policymaking. A racial disparity reform is a policy that seeks to reduce distinctions in criminal justice institutions’ treatment of racial groups. Elected officials pursue these policies due to ideological beliefs in civil rights ideals and political interests in appearing to solve social problems. Using an original database of policy enactments, this article first presents the distribution and types of reform measures adopted by elected officials in all 50 states between 1998 and 2011. It then examines social and political explanations for when state legislatures and executives adopt racial disparity reforms. Policy enactment is predicted by worsening problems of racial disproportion in criminal processing, Democratic control of elected branches, and the absence of judicial efforts to improve racial fairness within a state’s criminal justice system. Similar dynamics encourage the development of different measures types within policies. Such ideological and problem-solving explanations for racial disparity reform show a potential for elected officials to forge more racially just criminal justice practices.